INJURY DISORDERS OF NORTH SUMATRA PENCAK SILAT ATHLETES AT THE REGIONAL TRAINING CAMP LEADING UP TO THE XXI NATIONAL SPORTS WEEK - Al Munawar, Ahmad (Indonesia Sport Journal, 2023)
Injury is an abnormality in a person's organs that attacks both the functional and anatomical aspects of the body. Injuries that occur in athletes are usually caused by muscle fatigue from continuous use or due to physical contact that occurs in the competition arena. Injuries are a frightening "ghost" for athletes, especially during competitions, many athletes show poor performance due to fear of a recurrence of the injury. If injury treatment is not carried out seriously, in a scheduled, measurable and complete manner, the athlete will suffer the pain of the injury for the rest of his life. This research will capture and reveal clearly the types of injuries suffered by North Sumatra Pencak Silat athletes at Platda PON XXI who will compete in 2024. As the host, of course North Sumatra will not miss this prestigious event to show the best results, however the athlete's readiness is everything. -everything. The North Sumatra Youth and Sports Service, in collaboration with the North Sumatra Indonesian National Sports Committee, must be able to project and map the mental state of the athletes who will compete, any injuries they have, and also their physical readiness before competing.This research aims to assist the relevant agencies in mapping and projecting injury disorders, especially in XXI PON Pelatda pencak silat athletes. It is not uncommon for athletes to hide their injuries by focusing on maximum performance. This is considered very dangerous because the injury will be permanent for the athlete. This research uses a persuasive approach and questionnaire to record the types of injuries suffered by athletes.